1977
DOI: 10.1056/nejm197708112970603
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preoperative and Postoperative Bone Scanning in the Management of Breast Carcinoma

Abstract: With use of 99mtechnetium-labeled phosphates, we performed preoperative bone scans on 122 women with biopsy-proved breast carcinoma. Only two of the 110 patients with Stage I or II disease had scan abnormalities interpreted as bone metastases. Of 55 patients with normal preoperative scans, 20 later had changes suggesting bone metastases on the subsequent scans, most within 24 months of operation. In women with Stage I and II tumors, 13 of 48 (27 per cent) had scan evidence of bone metastasis of postoperative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The high incidence of skeletal metastasis in cancer patients warrants careful detection with imaging and follow-up (Gerber et al, 1977;Tarin et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence of skeletal metastasis in cancer patients warrants careful detection with imaging and follow-up (Gerber et al, 1977;Tarin et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…identifying metastasis (Gerber et al, 1977) and for preoperative assessment of resectablility (Tang et al, 2013). The evaluation of tumor by measuring lesion volume with the help of a radiologist and oncologist has become a standard procedure.…”
Section: Importance Of Volumetric Measurement Processes In Oncology Imentioning
confidence: 99%
“…So, the structure was assigned as 1,11-dihydroxy-8-methyl-naphthacene-5,12-dione (278) but not as 1,11-dihydroxy-9-methyl-naphthacene-5,12-dione (279). Angular quinones are excluded by the HMBC coupling of H-11 with 12-CO.…”
Section: Cinerubin Bmentioning
confidence: 98%
“…Phenazine derivatives show antibiotic properties and are characterized by their inhibitory activities against xanthine oxidase [105,279] . Phencomycin (179a) and its methyl ester (179b) were isolated from Streptomyces sp.…”
Section: -Methyl-510-dihydro-phenazine-16-dicarboxylic Acid Diamidementioning
confidence: 99%
“…Since its introduction into the clinical practice in the late 1960s [32,33], a large number of studies have been published on the value of BS as initial diagnostic test to detect the presence of skeletal metastases of BC at the time of primary presentation (table 1). However, the majority of these reports have suggested that the use of BS in the BC staging is of no benefit in the absence of symptoms or abnormal laboratory tests [4,5,[7][8][9][10][11][12][13][14].…”
Section: Is Bone Scan Recommended As Baseline Procedures For Primary Bmentioning
confidence: 99%